2009
DOI: 10.9775/kvfd.2012.6089
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional and Commercial Trichrome Staining Methods for Detecting Protozoan in Stool Samples

Abstract: ÖzetDışkının parazitolojik incelemesinde kalıcı boyama yöntemleri nativ-lugol incelemeye göre daha yüksek duyarlılık göstermesinin yanında, hazırlanan dışkı preparatlarının daha sonra incelenebilmesine olanak sağlaması ve protozoonların iç yapılarını tanımlanması nedeniyle tercih edilmektedir. Kalıcı boyama yöntemi olarak en sık trikrom boyama yöntemi kullanılmaktadır. Laboratuvarda hazırlanan konvansiyonel trikrom boyama çok basamaklı, hazırlaması ve uygulanması zahmetli olup, kısa sürede yapılan, az basamak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…They also stated that, because direct microscopy has a limited sensitivity, antigen detection procedures such as ELISA should be used to confirm diagnosis in individuals with suspected amoebiasis [36]. According to a 2012 study, persistent trichrome staining is the preferred approach of E.histolytica detection since it enables for later examination of faeces for identification of the protozoa's internal structure [37]. In 2014, researchers discovered that stool antigen testing by ELISA for the diagnosis of amoebiasis has 100% sensitivity and 100% specificity, and they advised that this technology be used as a diagnostic test [38].…”
Section: Discussionmentioning
confidence: 99%
“…They also stated that, because direct microscopy has a limited sensitivity, antigen detection procedures such as ELISA should be used to confirm diagnosis in individuals with suspected amoebiasis [36]. According to a 2012 study, persistent trichrome staining is the preferred approach of E.histolytica detection since it enables for later examination of faeces for identification of the protozoa's internal structure [37]. In 2014, researchers discovered that stool antigen testing by ELISA for the diagnosis of amoebiasis has 100% sensitivity and 100% specificity, and they advised that this technology be used as a diagnostic test [38].…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that, due to the low sensitivity of direct microscopy, the use of antigen detection methods by ELISA would be appropriate to confirm diagnosis in patients with suspected amoebiasis. Aydin et al [22] stated that the preferred method is permanent trichrome staining because it allows faeces to be examined later for the identification of the internal structure of the protozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Trikrom boyama dışında demir hematoksilen, giemsa, field ve wright boyaları da başarıyla kullanıl-maktadır. Kültür yöntemi Blastocystis tanısında duyarlılığı yüksek bir yöntemdir ancak zaman alıcı bir yöntem olup, sonuçların en az 2-3 gün beklenmesi ve bazı Blastocystis izolatlarının kültürde çoğalmaması gibi zorlukları bulunmaktadır (1,3,(12)(13)(14)(15) .…”
Section: Introductionunclassified
“…Kuruyan lamların üzerine kapatıcı (Eukitt ® Quick-hardening mounting medium, Fluka Biochemika, ABD) damlatılarak lamelle kapatıldı. Preparatlar immersiyon yağı kullanılarak ışık mikroskobunda 100x objektifte incelendi (15) .…”
Section: Introductionunclassified